Natural incidence of toxigenic Aspergillus flavus strains on the surface of pre-harvest jujube fruits - GEETA SUMBALI, YASH PAUL SINGH and (Indian Phytopathology, 2002)
Among the mycoflora on the surface of jujube (Ziziphus mauritiana) fruits, Aspergillus flavus was consistently recorded during the entire period of fruit development. Fifty isolates of A. flavus isolated from the preharvest fruits were observed to cause extensive post-harvest rot of mature jujube when inoculated artificially. All of these isolates were also screened for their aflatoxigenic potential in mature jujube. Some 54% of the isolates tested positive for different aflatoxins (B1, B2, G1 andG2) and their level ranged from 31 to 2874 ppb which is very high as compared with the tolerance limit of 20 ppb fixed by WHO. This study demonstrates for the first time that mature jujube fruits are a favourable substrate for infection and aflatoxin production by A. flavus strains.